Sentija’s new model for determination of heart rate deflection point (HRDP) does not have agreement with the maximal lactate steady state (MLSS) - معرفت سیاه کوهیان; صمد اسمعیل زاده (فیزیولوژی ورزش و فعالیت بدنی)
Background and aims: Recently Sentija et al. have validated and introduced a fast running exhaustive test (Tfast) for determination of heart rate deflection point (HRDP). However, the proposed test is not according to the recommended standards in the literature. Therefore, the present study aimed to examine the agreement between the HRDP determined by the Tfast and the maximal lactate steady state model (MLSS).Methods: Eleven young wrestler men underwent on subsequent occasions of a series of constant-velocity treadmill runs to determine MLSS. Heart rate data was obtained during the Tfast [speed increments of 1 km/h every 30 s] by using telemetry and HRDP was determined by using the S.Dmax model. Inter-observer reliability was analyzed using Bland-Altman plots and by determination of the Intraclass Correlation Coefficient (ICC).Results: The results indicated poor agreement between HRDP and HR of the criterion method (HRMLSS) (±1.96; 95% CI= -9.7 to +18.8 b/min; ICC= -0.09). Furthermore, poor agreement was observed between speed at HRDP (SpeedHRDP) and speed of the criterion method (SpeedMLSS) (±1.96; 95% CI= -2.3 to +3.9 km/h; ICC= 0.40).Conclusion: According to the results it is concluded that the proposed protocol (Tfast) by Sentija et al cannot be used as a reliable method instead criterion method (MLSS). Therefore the Tfast is not recommended for efficient running intensity prescription.